From pleasure and pride to the fear of decline: Exploring the emotions in older women's physical activity narratives. (November 2017) - Bennett, Erica V.; Hurd Clarke, Laura; Kowalski, Kent C.; Crocker, Peter R.E.
Abstract: Objectives: The purpose of this study was to explore the emotion narratives in older women's ageing body and physical activity-related stories. Method: The study was informed by narrative inquiry. We conducted two semi-structured interviews with 21 women aged 65 to 94 and asked them about their physical activity engagement, and body perceptions, experiences, and management strategies. Using thematic narrative analysis, we analysed the content of participants' stories pertaining to physical activity, the core patterns within them, and considered the cultural context in which they were embedded. Results: Emotion narratives of anxiety/fear, shame, guilt, pride, and pleasure permeated the women's stories. Participants feared physical and cognitive decline, and engaged in physical activity to stave off the ageing process. Body-related shame and guilt transected their stories; they were frustrated by their inabilities to engage in certain activities and with their move away from the healthy and physically fit cultural ideal. To negotiate this body-related anxiety/fear, shame, and guilt, the women drew attention to their accomplishments in the physical domain with pride, reinforcing their efforts to take personal responsibility for their health. Participants were also physically active for pleasure, gaining satisfaction from the social connections and mindfulness derived from being active, and through their participation in challenging yet rewarding activities. Conclusions: The findings are novel as they highlight the importance of cultural age and body norms coupled with complex emotional experiences in shaping later life physical activity experiences, and draw attention to the usefulness of stories to explore emotions in the physical domain. Highlights: Women were anxious about/feared physical and cognitive decline. Guilt and shame were experienced in relation to age-related body changes. Participants engaged in physical activity to slow body decline. Women discussed their accomplishments in the physical domain with pride. Participants derived pleasure from physical activity.